Upregulation and axonal transport of synaptotagmin‐IV in the direct‐pathway medium spiny neurons in hemi‐parkinsonian rats induced by dopamine D1 receptor stimulation. (23rd February 2016) - Tratnjek, Larisa; Glavan, Gordana; Višnjar, Tanja; Živin, Marko
Abstract: Synaptotagmin‐IV (Syt‐IV) may function as a regulator of Ca 2+ ‐dependent synaptic transmission. In the hemi‐parkinsonian rats with unilateral lesions of dopaminergic nigrostriatal neurons Syt‐IV and substance‐P (SP) mRNAs could be upregulated within the dopaminergically hypersensitive striatum of the lesioned brain hemisphere via the stimulation of striatal dopamine D1 (D1‐R), but not D2 receptors. The hypersensitive D1‐R‐mediated transmission may be the culprit for the undesired expression of levodopa‐induced dyskinesia, implying the involvement of Syt‐IV and SP in the process. First, striatal cellular phenotypes expressing Syt‐IV were determined. It was found to be expressed in all striatal neurons and a small population of astrocytes. Then it was examined, if the D1‐R‐mediated upregulation of Syt‐IV mRNA may result in the upregulation of the translated protein. It was found that, after acute stimulation with a selective D1 agonist, (±)‐6‐chloro‐7, 8‐dihydroxy‐3‐allyl‐1‐phenyl‐2, 3, 4, 5‐tetrahydro‐1H‐3‐benzazepine hydrobromide (SKF‐82958), Syt‐IV was elevated within the SP‐expressing striatal neurons of the lesioned side. This was followed by the upregulation of Syt‐IV, but not of its mRNA, within the ipsilateral target nuclei of the direct‐pathway medium spiny neurons, indicating axonal transport of de novo synthesized protein to their SP‐positive synaptic terminals. However, despite the striatal upregulation of SP and Syt‐IV following a similar time‐course, their subcellular co‐localization within the axonal terminals was not found. It was therefore suggested that Syt‐IV may regulate the hypersensitive striatal synaptic transmission, although via a SP‐independent mechanism. Abstract : D1‐stimulation up‐regulates Syt‐IV protein in the hypersensitive ipsilateral striatum of hemi‐parkinsonian rats in substance‐P positive direct pathway medium spiny neurons (MSNs). This is followed by Syt‐IV protein up‐regulation, but not of its mRNA, within the ipsilateral entopeduncular nucleus and substantia nigra pars reticulata, target nuclei of direct pathway MSNs, indicating axonal transport of de novo synthesized protein from the striatum to the target nuclei.